2014
DOI: 10.1111/bju.12557
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and health‐related quality of life (HRQL) in patients undergoing active surveillance of prostate cancer in an Australian centre

Abstract: Objective To assess anxiety, health‐related quality of life (HRQL) and understanding of active surveillance (AS) in a cohort of patients enrolled in AS of prostate cancer in an Australian setting. Patients and Methods Survey of 61 men currently enrolled in AS for prostate cancer, which included validated measures of sexual function using the International Index of Erectile Function (IIEF‐5), voiding using the International Prostate Symptom Severity Score (IPSS) and the Memorial Anxiety Scale for Prostate Cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 26 publications
0
37
1
Order By: Relevance
“…There was a low frequency of general and disease-specific anxiety in all five AS studies that assessed anxiety (usually in the range of 4-15%) [19,21,22,24,27]. Two studies also highlighted that anxiety scores of AS patients were comparable to those of radical prostatectomy patients [19,21].…”
Section: Anxietymentioning
confidence: 95%
See 1 more Smart Citation
“…There was a low frequency of general and disease-specific anxiety in all five AS studies that assessed anxiety (usually in the range of 4-15%) [19,21,22,24,27]. Two studies also highlighted that anxiety scores of AS patients were comparable to those of radical prostatectomy patients [19,21].…”
Section: Anxietymentioning
confidence: 95%
“…More generally, since the values scored by both men and their partners were within the normal range of the general population, the authors concluded that anxiety for these individuals was not clinically relevant. Similarly, Wilcox et al [27] underlined that the level of anxiety relating specifically to PCa in a cohort of Australian patients on AS was below the defined threshold of clinical relevance.…”
Section: Anxietymentioning
confidence: 99%
“…8 Active surveillance consists of close observation via a regimen of periodic PSA measurements, digital rectal examinations and serial prostate biopsies, with the goal of offering curative therapy in the event of disease progression or reclassification. Evidence suggests that active surveillance for low-grade prostate cancer is a safe and feasible management option that is well tolerated by patients 9,10 and does not substantially compromise oncologic outcomes. 11,12 Although a variety of selection criteria for active surveillance exist, most patients with a diagnosis of low-grade (Gleason score 6) cancer may be candidates.…”
mentioning
confidence: 99%
“…Anderson et al [25] found that trait anxiety and fear of recurrence were significant predictors for both PCa-related and total HRQoL. Wilcox et al [26] reported on 47 active surveillance patients who had completed HRQoL measures in an Australasian setting. Their results did not differ from those reported in other groups of men on active surveillance.…”
Section: Published Active Surveillance Short-term Follow-up Outcomesmentioning
confidence: 99%